Mapping land subsidence over the eastern Beijing city using satellite radar interferometry - Zheyuan Du; Linlin Ge; Alex Hay-Man Ng; Li Xiaojing; Liyuan Li (International Journal of Digital Earth, 2018)
Beijing City has suffered from groundwater-induced subsidence since the late 1930s and the over-exploration of groundwater could lead to subsidence as much as −12.0 cm yr−1. Previous studies on the ground deformation at Beijing City mainly focused on the period before the year of 2014 when a mega-engineering project was launched to reduce water shortage in Beijing. To study the most recent ground deformation, 19 L-band ALOS-1 PALSAR images (June 2007–January 2011), 24 C-band Sentinel-1 SAR images (June 2015–November 2016) together with 9 ALOS-2 PALSAR acquisitions (September 2014–February 2017) were analysed in this work. Levelling measurements were exploited to verify the ALOS-1-based time series InSAR (TS-InSAR) result while Sentinel-1 and ALOS-2 result were cross-verified with each other. Furthermore, the whole study area was divided into four sub-zones, and the result indicated that the subsidence rates over five townships, Cuigezhuan, Jinzhan, Liyuan, Songzhuang and Yanjiao were accelerating and more attentions should be paid. On the contrary, the town centre of Douge Zhuang township experienced a decreasing trend between these two temporal-periods. Additionally, the time series measurements with respect to five selected measurement points and the profile line along the subsidence hot spots were analysed.